Psoriasis With Leg Involvement, a New Difficult-to-Treat Area: A Cohort Study of Patients Treated With Risankizumab - Bardazzi, Federico; Filippi, Federica; Mussi, Martina; Lasagni, Claudia; Bigi, Laura; Odorici, Giulia; Peccerillo, Francesca; Rovesti, Miriam; Satolli, Francesca; Tabanelli, Michela; Schianchi, Sandra; Di Lernia, Vito; et al. (Dermatology Practical & Conceptual, 2024)
Introduction: Historically, difficult-to-treat areas in psoriasis included face, scalp, folds, genitalia, nails and palmoplantar region. Recent studies have found that lower limbs behave like a “new” difficult-to-treat area, as it can be the only site of residual disease even in patients undergoing biologic therapies.Objectives: We aimed to evaluate whether legs had different response rates and response times to treatment with a new biologic drug, risankizumab, than other body sites.Methods: We conducted a real-life, observational, retrospective, multicentric study, including patients affected by moderate-to-severe psoriasis with legs involvement and undergoing biological therapy with risankizumab for more than 16 weeks. The Psoriasis Area Severity Index (PASI) and Leg-PASI were collected at T0 and at week 16, 28, 40, 52, 64 and 76. Statistical analysis using T student test and linear regression analysis were performed.Results: A total of 124 patients were included. The difference between the improvement percentage respect to baseline was statistically significant at week 16 and 28, demonstrating that Leg-PASI improved less than PASI. From the linear regression it was deduced that the slope is statistically less steep for Leg-PASI than for overall PASI, confirming that this site responds more slowly to the therapy.Conclusions: Leg response to risankizumab appears to differ significantly from other body-sites in the first weeks of treatment, even if after 28 weeks statistical significance is lost. Our preliminary finding suggests that risankizumab can be considered an effective treatment for legs psoriasis, but with longer response times than other areas demonstrating the relative nature of resistance to treatment of this district.